2003
DOI: 10.1177/104063870301500409
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory Response of Dairy Cows Fed Ergotized Barley during Summer Heat Stress

Abstract: Claviceps purpurea infects the seed heads of cereal grains and grasses and produces ergopeptine alkaloids that cause hyperthermia and agalactia in cattle during periods of heat stress. A field experiment was undertaken to examine the effects of ergopeptine alkaloids found in barley on thermal status of dairy cattle during periods of heat stress. Production end points were also measured to identify the effect of the change in thermal status. Contaminated barley screenings containing known levels of ergopeptine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…But due to the observed marginal symptoms of ergot toxicosis reflected in body temperature and milk production, the author suggested this alkaloid dose as a level for minimal induction of the ergot toxicity response (AlTamimi et al 2003). Considering that Al-Tamimi et al (2003) used ergotized barley, which probably also contained ergometrine and its isomere, the only alkaloids analysed in the current study, which do not belong to the ergopeptine group, the total alkaloid administration might have been a little higher. The current study revealed a percentage of 93% ergopeptine alkaloids of the total alkaloid amount ( Table I).…”
Section: Performance and Carcass Compositionmentioning
confidence: 85%
See 2 more Smart Citations
“…But due to the observed marginal symptoms of ergot toxicosis reflected in body temperature and milk production, the author suggested this alkaloid dose as a level for minimal induction of the ergot toxicity response (AlTamimi et al 2003). Considering that Al-Tamimi et al (2003) used ergotized barley, which probably also contained ergometrine and its isomere, the only alkaloids analysed in the current study, which do not belong to the ergopeptine group, the total alkaloid administration might have been a little higher. The current study revealed a percentage of 93% ergopeptine alkaloids of the total alkaloid amount ( Table I).…”
Section: Performance and Carcass Compositionmentioning
confidence: 85%
“…As the average total daily alkaloid exposure in the current experiment did not exceed 9 mg per kg LW (8.4 mg ergopeptine alkaloids per kg LW), it might have been low enough to be completely tolerated by the animals, but following Al-Tamimi et al (2003) this dose would then be very close to the no-effect level.…”
Section: Performance and Carcass Compositionmentioning
confidence: 90%
See 1 more Smart Citation
“…Na reprodução experimental, o quadro clínico de hipertermia ocorreu nos períodos mais quentes do dia, e está de acordo com o descrito para a intoxicação por C. purpurea (Al-Tamimi et al 2003). Já o Bovino 5 que ingeriu as inflorescências infectadas nos dias mais amenos não manifestou estes sinais.…”
Section: Intoxicação Experimentalunclassified
“…In August 1996, there was an outbreak in the United States. Several cattle herds in Northeast Iowa and Southwest Wisconsin suffered from hyperthermic ergotism after eating infected barley (Al-Tamimi et al, 2003).…”
Section: Cattle Outbreaksmentioning
confidence: 99%